Positive correlation between n- 6 : n- 3 PUFA ratio intake with serum oxHDL/HDL-c ratio in patients with coronary artery disease - Godinez-Mora, Sissi; Campos-Perez, Wendy; Perez-Robles, Mariana; Robles-Jimarez, Cesar; Muñoz-Hernandez, Alejandra; Torres-Vanegas, Joel; Martinez-Lopez, Erika (Coronary artery disease, 2025)
Coronary artery disease (CAD) is one of the most prevalent cardiovascular diseases where serum lipoprotein oxidation plays a significant role. Polyunsaturated fatty acids (PUFA) n -6 :  n -3 unbalance ratio consumption, affects lipoprotein oxidation, and inflammation processes. This study aimed to analyze the relationship between n -6 :  n -3 PUFA ratio intake with oxidized lipoproteins in individuals with CAD. A cross-sectional study was performed including 105 subjects (51 diagnosed with CAD and 54 non-CAD) from western Mexico. Dietary information was collected using a habitual day food record. Serum oxidized low-density lipoprotein (oxLDL) and oxidized high-density lipoprotein (oxHDL) concentrations were quantified by enzyme linked immunosorbent assay. CAD subjects had higher oxHDL/HDL cholesterol (HDL-c) ratio [0.102 (0.092-0.112) vs. 0.080 (0.070-0.090), P  = 0.004] and oxLDL/LDL cholesterol (LDL-c) ratio [129.2 (108-150.4) vs. 59.7 (39.3-80), P  < 0.001] compared to non-CAD subjects. Risk factors associated with CAD were a high n -6 :  n -3 PUFA ratio (odds ratio, OR = 2.3, P  = 0.046), hypoalphalipoproteinemia in men (OR = 3.2, P  = 0.014), moderate/high tobacco index (OR = 6.33, P  = 0.003), elevated waist circumference in women (OR = 7, P  = 0.004), hypertension (OR = 21.14, P  < 0.001), and type 2 diabetes (OR: 25, P  < 0.001). The oxHDL/HDL-c ratio was positively associated with the n -6 :  n -3 PUFA ratio [ r2  = 28.3, B  = 0.002 (0.001-0.003), P  < 0.001] in CAD patients. This study showed that a higher n -6 :  n -3 PUFA ratio intake correlates with higher serum oxHDL/HDL-c in CAD patients.